Conductive adhesive as well as preparation method and application thereof

Through efficient mixing of materials such as synthesis of acrylic resins, epoxy resins and conductive fillers, the problem of low curing activity of conductive glue is solved, and the long storage time and excellent performance of conductive glue is achieved, which is suitable for the diversified needs of electronic products.

CN119307200AActive Publication Date: 2025-01-14深圳市蓝特电路板有限公司 +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411458831.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-14
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The curing activity of existing conductive adhesives is low, which makes it difficult to ensure stable performance and storage time at room temperature, affecting its application scenarios and production efficiency.

Method used

Using synthetic acrylic resins, epoxy resins, conductive fillers, latent curing additives and diluents, conductive adhesives with excellent bonding properties, conductive properties and long storage time are prepared through efficient mixing and dispersing technology.

Benefits of technology

It improves the storage time and overall performance of conductive adhesives, simplifies production processes, reduces costs, and adapts to the needs of different application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of conductive adhesives, and particularly relates to a conductive adhesive as well as a preparation method and application thereof, and the conductive adhesive is prepared from the following raw materials in parts by weight: 40-60 parts of synthetic acrylic resin, 5-15 parts of epoxy resin, 25-45 parts of conductive filler, 5-15 parts of latent curing aid, 80-120 parts of diluent and 5-8 parts of aid. By adding the latent curing aid, the potential possibility of reaction of the acrylic resin and the epoxy resin at normal temperature can be reduced, so that the storage effect of the conductive adhesive is improved, the overall performance of an electronic product can be improved, and application scenes with different requirements can be met; according to the preparation method, the raw materials such as the acrylic resin, the epoxy resin, the conductive filler, the auxiliary agent, the diluent and the latent curing auxiliary agent are directly and uniformly mixed in the preparation process without separate storage, so that the production cost is reduced, the use process of a user is simplified, and the production efficiency and the product quality of the conductive adhesive can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductive adhesives, and in particular relates to a conductive adhesive, and a preparation method and application thereof. Background Art

[0002] With the progress of society and the development of science and technology, electronic products are increasingly used in our daily lives, and the requirements for product performance are also getting higher and higher. Especially in some key areas, such as communications, medical care, and military, the stability and reliability requirements of components are more stringent. Shielding function is one of the important means to ensure the stable operation of components. Through shielding, the influence of external electromagnetic interference on components can be effectively prevented, and the performance and stability of products can be improved. For example, in electronic devices such as mobile phones, if components are subject to external interference, problems such as screen distortion, black screen, and inconsistent photo effects may occur, which seriously affect the user experience. Therefore, strengthening the shielding function of electronic components is of great significance to improving the overall performance and user experience of electronic products.

[0003] The conductive adhesive film currently used for shielding conductive grounding on the market is a commonly used shielding material, mainly used for conductive grounding and shielding of electronic components. It has good conductivity and adhesion properties, and can effectively isolate components from the outside world to prevent the intrusion of electromagnetic interference. The curing activity of existing conductive adhesive films is relatively low. These products require refrigeration during use to increase their shelf life. It is difficult to ensure the performance stability and operability of the products at room temperature. The main body of some products needs to be separated from the curing agent and mixed during preparation to avoid premature reaction and curing of the conductive adhesive. This brings inconvenience to the user's production, thereby affecting efficiency and limiting the application scenarios of the conductive adhesive. Therefore, it is necessary to develop a conductive adhesive that can extend the shelf life without affecting its performance, as well as its preparation method and application, so as to improve the overall performance of electronic products and meet application scenarios with different needs. Summary of the invention

[0004] The purpose of the present invention is to overcome the disadvantages of the above-mentioned conductive adhesive and provide a conductive adhesive.

[0005] The present invention adopts the following technical solutions: A conductive adhesive is prepared from the following raw materials in parts by weight: 40-60 parts of synthetic acrylic resin, 5-15 parts of epoxy resin, 25-45 parts of conductive filler, 5-15 parts of latent curing auxiliary agent, 80-120 parts of diluent and 5-8 parts of auxiliary agent.

[0006] Specifically, synthetic acrylic resin has good bonding properties and weather resistance, and can provide a stable matrix for conductive adhesive. Additionally, epoxy resin has excellent bonding properties and mechanical strength. Adding epoxy resin to conductive adhesive can further improve the bonding force and durability of the colloid. Furthermore, by adding conductive fillers, the resistivity of the colloid can be significantly reduced, and the conductive properties can be improved. Preferably, latent curing aids can adjust the curing speed, hardness and temperature resistance of the conductive adhesive at different temperatures, thereby improving the storage time of the conductive adhesive at room temperature. Additionally, diluents are used to adjust the viscosity and fluidity of the conductive adhesive for construction operations. Additionally, additives help to improve the stability of the colloid and the dispersibility of the filler, thereby improving the overall performance of the colloid.

[0007] Furthermore, the synthetic acrylic resin is synthesized from methyl acrylate, methyl methacrylate, glycidyl methacrylate, styrene and methacrylic acid.

[0008] Specifically, methyl acrylate itself has good weather resistance and adhesion, and can be used as a soft monomer to provide the resin with flexibility and adhesion; in addition, methyl methacrylate, as a hard monomer, can increase the hardness, wear resistance and transparency of the resin; furthermore, glycidyl methacrylate contains epoxy groups, which can undergo cross-linking reactions with other resins or curing agents, thereby improving the hardness, adhesion, heat resistance and chemical resistance of the resin; in addition, styrene can increase the rigidity and heat deformation temperature of the resin, and can improve the high temperature stability and impact resistance of the colloid; at the same time, methacrylic acid introduces a carboxyl functional group to increase the polarity and hydrophilicity of the resin, thereby adjusting the viscosity and fluidity of the resin and facilitating the wetting and dispersion of the conductive filler.

[0009] Furthermore, the epoxy resin includes trifunctional alicyclic epoxy resin and bisphenol A epoxy resin.

[0010] Specifically, trifunctional alicyclic epoxy resin has high crosslinking density, chemical resistance and mechanical properties. Trifunctional alicyclic epoxy resin can provide strong adhesion and durability, thus ensuring that the conductive adhesive can maintain stable performance in various environments. At the same time, its high crosslinking density also helps to improve the shielding effect and anti-interference ability of the conductive adhesive, while having a higher glass transition temperature (Tg) and better heat resistance.

[0011] Specifically, bisphenol A epoxy resin has good flexibility and bonding properties, chemical resistance and electrical insulation properties, and has good adhesion to a variety of substrates. Its good physical and mechanical properties can increase the strength and toughness of the conductive adhesive and improve its durability during application. Bisphenol A epoxy resin and trifunctional alicyclic epoxy resin work synergistically to further improve the comprehensive performance of the conductive adhesive. At the same time, its good electrical insulation properties also help reduce the risk of leakage during the use of the conductive adhesive.

[0012] Specifically, by adding trifunctional alicyclic epoxy resin and bisphenol A epoxy resin, a certain degree of flexibility can be added while maintaining good mechanical strength, thereby improving the overall mechanical properties of the conductive adhesive, while ensuring the bonding effect of the conductive adhesive on different substrates, improving its application range and reliability, and balancing the heat resistance of the two, so that the conductive adhesive can still maintain good performance in a high temperature environment. In addition, the trifunctional alicyclic epoxy resin with a large cross-linking density and a high curing temperature is mixed with the bisphenol A epoxy resin with a low viscosity and a low curing temperature, which is easy to process and coat.

[0013] Preferably, the ratio of the trifunctional alicyclic epoxy resin to the bisphenol A epoxy resin of the epoxy resin is 3:7-5:5. By such a configuration, not only can the hardness and flexibility of the resin be taken into account, thereby balancing the mechanical properties, but also the heat resistance can be optimized by improving the stability at high temperatures. Furthermore, by utilizing good adhesion to a variety of substrates to enhance the bonding performance, and adapting to different curing conditions to improve the curing characteristics, improve the processing performance for easy coating and operation, the overall performance of the conductive adhesive can be improved.

[0014] Furthermore, the conductive filler includes at least two or more of silver-coated polystyrene microspheres, modified carbon nanotubes, silver powder, and modified expanded graphite. Specifically, the silver-coated polystyrene microspheres can reduce the overall density of the material and reduce the overall cost of the conductive adhesive. By highly dispersing silver nanoparticles on the surface of the polystyrene microspheres, utilizing the high conductivity of silver and the three-dimensional structure of the polystyrene microspheres, high electromagnetic interference shielding efficiency can be achieved at a low metal content, which helps to improve the conductive performance and mechanical stability of the conductive adhesive.

[0015] Specifically, the modified carbon nanotubes of the present invention are obtained by surface-modifying the original carbon nanotubes by chemical methods. The modified carbon nanotubes have better dispersibility and compatibility with the matrix resin, thereby more effectively improving the conductive properties of the conductive adhesive. At the same time, the carbon nanotubes also have excellent mechanical properties and thermal stability, which can enhance the overall performance of the conductive adhesive.

[0016] Specifically, the modified carbon nanotubes of the present invention are carboxylated carbon nanotubes, which have better dispersibility in solvents and can be evenly dispersed with modified expanded graphite. The carboxyl group can form hydrogen bonds or covalent bonds with the functional groups on the surface of the modified expanded graphite, thereby enhancing the interface bonding force.

[0017] The method for preparing modified carbon nanotubes comprises the following steps: P1. Concentrated nitric acid and concentrated sulfuric acid are prepared according to a volume ratio to form a mixed acid solution, and the multi-walled carbon nanotube solution is slowly added into the mixed acid solution while continuously stirring; P2, perform ultrasonic treatment at 50-80°C for 4-6 hours, after the ultrasonic treatment, heat and stir, and reflux at 50-60°C for 3 hours to obtain a reaction solution; P3. Slowly pour the reaction solution into a vessel containing deionized water, cool it, and then filter it. Rinse it with a large amount of deionized water until the pH is close to 7. Vacuum dry the acidified carbon nanotubes at 70-90°C for 12 hours to obtain carboxylated carbon nanotubes.

[0018] Specifically, silver powder has excellent electrical conductivity and stability. In the conductive glue, silver powder can provide a continuous conductive path to ensure smooth transmission of electrons. Silver powder can also increase the filling density of the conductive glue, thereby improving its electrical conductivity and mechanical strength. Preferably, the present invention uses flaky silver powder, because its particles are in line contact or surface contact, compared with the point contact of spherical silver powder, the flaky silver powder has a relatively low resistance, the specific surface area of ​​the flaky silver powder is larger than that of the spherical silver powder, and the surface activation energy is lower than that of the spherical or quasi-spherical silver powder, so its oxidation degree and oxidation tendency are lower, and the flaky silver powder has a wider deflection range and anti-fracture and elongation characteristics, which helps to enhance the deformation resistance of electronic components when subjected to external forces.

[0019] Specifically, compared with the original graphite, the modified expanded graphite has a larger specific surface area and better dispersibility, forming more conductive channels in the conductive adhesive, thereby improving the conductive performance. At the same time, the expanded graphite also has excellent high temperature resistance and chemical stability, so that the conductive adhesive can still maintain good performance under high temperature and harsh environment.

[0020] Further, the modified expanded graphite used in the present invention is a material after ZIF-7 and expanded graphite are compounded, and the modified expanded graphite after ZIF-7 and expanded graphite are compounded has significant beneficial effects as a conductive filler, including improving electrical conductivity, enhancing mechanical properties, improving thermal stability and optimizing interface compatibility, and specifically, expanded graphite has a larger specific surface area and a porous structure, which helps to form a conductive network in a polymer matrix, thereby reducing the percolation value, reaching the critical volume fraction of filler required for the conductive state, and the ZIF-7 material has a regular pore structure and a higher specific surface area, which is conducive to improving electrical conductivity. When ZIF-7 is compounded with expanded graphite, the advantages of the two can complement each other, thereby further improving electrical conductivity. The lamellar structure of expanded graphite can increase the toughness and strength of the composite material, and the porous structure of ZIF-7 helps to absorb external stress and prevent crack propagation, and this synergistic effect makes the composite material have excellent mechanical properties while maintaining good electrical conductivity. ZIF-7 material has high thermal stability, which helps to improve the heat resistance of the composite material. When compounded with expanded graphite, the synergistic effect of the two can further improve the thermal stability of the composite material, allowing it to maintain good conductivity and mechanical properties in high temperature environments.

[0021] Specifically, the preparation method of modified expanded graphite is: Q1. Dissolve zinc nitrate hexahydrate and 2-methylimidazole in methanol, stir vigorously, centrifuge, wash with anhydrous methanol to obtain white powder, and vacuum dry to obtain ZIF-7 crystals; Q2. Add natural flake graphite to concentrated sulfuric acid, stir evenly, slowly add sodium nitrate, continue stirring and add potassium permanganate in batches, control the temperature between 20-30℃ to avoid violent reaction. After 4 hours of reaction, add deionized water to dilute, and then add hydrogen peroxide to stop the reaction; after washing and drying, put it in a high-temperature furnace, heat it quickly at 800-1000℃ to make it expand, and get expanded graphite after cooling.

[0022] Q3, ZIF-7 and expanded graphite were added to ethanol, polyvinyl pyrrolidone and silane coupling agent were added, stirring was continued for 1 hour, and the mixture was placed in an ultrasonic cleaner for 30 minutes; Q4. Filter the mixed solution after ultrasonic treatment, collect the solid part, wash it with ethanol, and vacuum dry it at 60°C for 12 hours.

[0023] Furthermore, the high aspect ratio and hydrophilicity of carbon nanotubes after carboxylation can form a uniform three-dimensional network with ZIF-7 and expanded graphite, further enhancing the electrical conductivity and mechanical strength, while providing excellent dispersibility and bonding strength. The synergy of flaky silver powder with ZIF-7 and expanded graphite can form a multi-level conductive network, further reducing resistance and improving electrical conductivity. At the same time, the flaky structure helps to enhance the mechanical properties and thermal conductivity of the composite material. The porous structure of the modified expanded graphite helps to improve the dispersion of silver-coated polystyrene microspheres in the matrix, thereby improving the overall performance of the composite material, and can also prevent oxidation and agglomeration of silver-coated polystyrene microspheres, maintaining the stability of the material.

[0024] Furthermore, the latent curing aid includes one or more of a phenolic amine curing agent and a curing accelerator, the diluent includes one or more of butyl glycidyl ether and phenyl glycidyl ether, the aid includes ammonia water and a silane coupling agent, the curing accelerator includes one or both of SH-A100 or 2-ethyl-4-methylimidazole, and the silane coupling agent includes one or both of γ-glycidyloxypropyltrimethoxysilane or γ-aminopropyltriethoxysilane.

[0025] Specifically, the phenolic amine curing agent can undergo a cross-linking reaction with a matrix resin such as epoxy resin to form a cured product with excellent performance. In the conductive adhesive, the phenolic amine curing agent can provide strong adhesion and durability, ensuring that the conductive adhesive can maintain stable performance in various environments. At the same time, the phenolic amine curing agent is latent and is not easy to undergo a cross-linking reaction with a matrix resin such as epoxy resin at room temperature. The curing accelerator can accelerate the curing reaction. Specifically, it can reduce the activation energy of the curing reaction and increase the reaction rate, thereby shortening the curing time of the conductive adhesive. Preferably, SH-A100 is a urea modified material that does not cure at room temperature, can be stored at room temperature for more than half a year, and can be quickly cured at 120-130°C. Preferably, 2-ethyl-4-methylimidazole is almost inactive at room temperature, but as the temperature rises to 130°C, its activity is significantly enhanced, which can effectively promote the curing reaction.

[0026] Compared with the existing conductive adhesive which is slowly cured at room temperature and difficult to store, the conductive adhesive of the present invention, with the cooperation of the phenolic amine curing agent and the curing accelerator, starts to activate and cure at above 130 degrees, and is completely cured in 30-60 minutes at 160 degrees. Therefore, the conductive adhesive of the present invention can be stored for a long time at room temperature and can react and cure at an appropriate temperature during the preparation process and the application process of the conductive adhesive.

[0027] Specifically, butyl glycidyl ether can reduce the viscosity of epoxy resin, improve processability, and enhance its fluidity and operability; phenyl glycidyl ether can enhance the flexibility and heat resistance of the cured product; butyl glycidyl ether and phenyl glycidyl ether can reduce the viscosity of the conductive adhesive; these two diluents also have a certain plasticizing effect, which can improve the flexibility and impact resistance of the conductive adhesive.

[0028] Specifically, ammonia water can neutralize the acidic components in the conductive adhesive and adjust the pH value, thereby improving the performance of the conductive adhesive. At the same time, ammonia water also has a certain catalytic effect and can accelerate the curing reaction.

[0029] Furthermore, silane coupling agents can improve the compatibility between inorganic fillers and organic matrices, and improve the dispersibility and stability of fillers. In conductive adhesives, silane coupling agents can enhance the interfacial bonding between inorganic fillers and matrix resins, thereby improving the overall performance of conductive adhesives. Specifically, γ-aminopropyltriethoxysilane has good hydrolysis stability and reactivity, can form covalent bonds with a variety of substrates (such as metals, glass, ceramics, etc.), and can enhance the interfacial bonding between conductive fillers and resins. γ-Glycidyloxypropyltrimethoxysilane has an epoxy group, which can react with amine or hydroxyl groups in the resin during the curing process to form a stable chemical bond, which can improve the compatibility and bonding strength between the filler and the resin.

[0030] Furthermore, the preparation method of the synthetic acrylic resin comprises the following steps: N1. Dissolve the monomer in the solvent according to the predetermined ratio, mix well and add to the reactor; add the weighed monomer to the reaction vessel, stir well, add ethyl acetate, and continue stirring to fully dissolve it. Add a small amount of stabilizer 4-methoxyphenol to prevent the polymerization reaction from starting at low temperature, and then add the mixed monomer solution to the reactor. The synthesized acrylic resin contains a specific ratio of methyl acrylate, methyl methacrylate, glycidyl methacrylate, styrene and methacrylic acid monomers. Methyl methacrylate can provide hardness and gloss, so that the conductive adhesive has good surface quality after curing. Glycidyl methacrylate introduces epoxy groups, increases the crosslinking and adhesion of the resin, and helps the stable dispersion of the conductive filler in the resin and the firm bonding with the substrate. Styrene improves the rigidity and chemical resistance of the resin, so that the conductive adhesive maintains stable performance under various environments. Methacrylic acid monomer can adjust the polarity and reactivity of the resin and enhance the compatibility with the conductive filler. Using ethyl acetate as a solvent enables the resin to form a uniform reaction system during the synthesis process, and when making conductive adhesive, ethyl acetate can be used as a good diluent to adjust the viscosity of the conductive adhesive, making it easy to coat, print or spray and other processing operations. Compared with ordinary acrylic resins on the market, synthetic acrylic resins are easier to control viscosity and fluidity during processing and adapt to different production process requirements.

[0031] N2. Add the initiator to the reactor; heat the reactor to a certain temperature and keep it constant; dissolve the initiator in a small amount of solvent and slowly add it to the reactor through a dripping device. Heat the reactor to 60-80℃ and keep it constant, stir continuously under constant temperature conditions, and the reaction time is 4-6 hours. The control of reaction conditions ensures that the degree of polymerization and molecular weight distribution of the resin are more uniform, so that it has better rheological properties and processing stability when making conductive adhesives. During the coating process, there will be no problems such as sagging, bubbling or uneven thickness, which improves the production quality and efficiency of conductive adhesives.

[0032] N3. After the polymerization is completed, the product is cooled, washed and dried. After the reaction is completed, stop heating and let the mixture cool naturally to room temperature. Use a filter to filter the mixture to remove unreacted solid particles. Wash several times with an appropriate amount of ethyl acetate to remove unreacted raw materials and impurities. Dry the washed product in a vacuum drying oven to remove the solvent. The drying temperature is 60-80°C and the drying time is 12-24 hours until the product is completely dry.

[0033] Furthermore, the preparation method of the phenalkamine curing agent comprises the following steps: P1. Dissolve dicyandiamide in a solvent, mix with formaldehyde, add a catalyst, and stir evenly; specifically, add dicyandiamide to a reaction container, add ethanol, and start stirring to fully disperse the dicyandiamide. Slowly add formaldehyde aqueous solution and continue stirring evenly. Add a few drops of hydrochloric acid catalyst and stir evenly.

[0034] P2. Gradually add phenol under stirring conditions to maintain the reaction temperature and pH value; Under stirring conditions, slowly add phenol, control the reaction temperature between 60-80°C, and continue stirring. Use a pH meter to monitor the pH value of the reaction mixture, and adjust the pH value to pH 7-8 with dilute hydrochloric acid or sodium hydroxide solution, and continue to stir the reaction mixture under a neutral or slightly alkaline environment for 2-4 hours until the reaction is completed.

[0035] P3. After the reaction is completed, cool the mixture to room temperature, and cool, wash and dry the product. After the reaction is completed, stop heating and let the mixture cool naturally to room temperature. Use a filter to filter the mixture to remove unreacted solid particles. Wash several times with an appropriate amount of ethanol solvent to remove unreacted raw materials and impurities. Dry the washed product in a vacuum drying oven to remove the solvent. The drying temperature is 60-80°C and the drying time is 12-24 hours until the product is completely dry.

[0036] Furthermore, another object of the present invention is to provide a method for preparing a conductive adhesive, comprising the following steps: S1. Add synthetic acrylic resin, epoxy resin, conductive filler and part of the additives to part of the diluent, put them into a double planetary mixer according to the weighed number of portions, and disperse them at high speed until all the materials are dissolved. Put them into a reactor with a double planetary mixer according to the weighed number of portions, stir and disperse them at high speed. The purpose of stirring and high-speed dispersion is to dissolve all the materials and form a uniform solution or suspension. The speed during high-speed dispersion is 400-600 rpm, and the high-speed dispersion time is 30-60 minutes.

[0037] S2, then add the latent curing aid, the remaining diluent and the remaining additives, mix evenly, then vacuum degas, filter and subpackage, and store at room temperature in a dry and ventilated environment. First, perform high-speed dispersion at 400-600 rpm until all materials are added, and then use high-speed dispersion at a speed of 800-1200 rpm, and the high-speed dispersion time is 3.5-4.5 hours. The addition of latent curing aids can provide longer storage time and better bonding performance. Put the mixed conductive adhesive into a vacuum degassing equipment, vacuum it, and keep the vacuum degree at about -0.09 MPa for 10-20 minutes until the bubbles disappear completely, so as to remove the bubbles generated during the mixing process, thereby improving the quality of the conductive adhesive. Filter and subpackage and dispense the conductive adhesive into suitable containers for subsequent use. Store at room temperature in a dry and ventilated environment to ensure the stability and service life of the conductive adhesive.

[0038] Furthermore, another object of the present invention is to provide an application of a conductive adhesive, wherein the conductive adhesive is applied to a coating film production process.

[0039] As a substitute for lead-free solder, conductive adhesive reduces environmental pollution and conforms to the development trend of green manufacturing. The coating production process can accurately control the coating thickness and uniformity of conductive adhesive to ensure the quality and performance of the product. The electrical connection formed by conductive adhesive is stable and reliable, which can improve the service life and stability of electronic products. Conductive adhesive can adapt to electronic components of various shapes and sizes to meet different application scenarios.

[0040] Specifically, the coating film production process includes the following steps: Y1: unwinding the carrier film and coating the conductive adhesive; Y2: Drying, cooling, winding, packaging, and shipping of finished products.

[0041] Specifically, after the conductive adhesive is coated on the carrier film and dried, in step Y2, the conductive adhesive is dried at 80-100° C. for 30 minutes, the conductive adhesive film layer is 35-45 μm thick, and the carrier release film layer is 55-65 μm thick.

[0042] Specifically, the conductive components include a steel sheet layer, a conductive film layer, a PI insulation layer, and a copper foil layer from top to bottom. The conductive film layer has excellent properties such as good peel strength, good high temperature resistance, and good conductivity. The conductive film layer can achieve the conduction between the copper foil layer and the steel sheet layer to achieve the shielding effect of the components.

[0043] Specifically, when producing conductive components, the conductive glue on the carrier release film is passed through a hot pressing roller at a temperature of 110-140 degrees, a pressure of 4-6 kg, and a speed of 1 minute / meter. One side of the conductive glue is connected to the steel sheet. The conductive adhesive tape has a carrier film surface. After the carrier release film is torn off, it is adhered to the PI surface. The fast pressing temperature of the conductive components is 180±5 degrees, pre-pressing for 10 seconds, molding for 120-180 seconds, and a pressure of 120±5 kg. After pressing, it is baked at 160 degrees for 60-90 minutes to stabilize the product.

[0044] Compared with the prior art, the present invention has the following advantages: 1. The present invention can reduce the potential possibility of acrylic resin and epoxy resin reacting at room temperature by adding a latent curing agent, thereby improving the storage effect of the conductive adhesive without affecting its use effect, thereby improving the overall performance of electronic products and meeting application scenarios with different needs.

[0045] 2. The preparation method of the present invention directly mixes raw materials such as acrylic resin, epoxy resin, conductive filler, additives, diluents and latent curing additives evenly during the preparation process without the need for separate storage, thereby reducing production costs and simplifying the user's use process, thereby improving the production efficiency and product quality of the conductive adhesive. DETAILED DESCRIPTION

[0046] In order to make those skilled in the art more clearly understand the technical solution of the present invention, the following examples are listed for illustration. Unless otherwise specified, the raw materials, reagents or devices used in the following embodiments can be obtained from conventional commercial channels or can be obtained by existing known methods.

[0047] The present invention will be further described below in conjunction with specific embodiments: A conductive adhesive is prepared from the following raw materials in parts by weight: 40-60 parts of synthetic acrylic resin, 5-15 parts of epoxy resin, 25-45 parts of conductive filler, 5-15 parts of latent curing auxiliary agent, 80-120 parts of diluent and 5-8 parts of auxiliary agent.

[0048] Furthermore, the epoxy resin includes trifunctional alicyclic epoxy resin and bisphenol A epoxy resin.

[0049] The ratio of the trifunctional alicyclic epoxy resin to the bisphenol A epoxy resin of the epoxy resin is 3:7-5:5.

[0050] The conductive filler comprises at least two or more of silver-coated polystyrene microspheres, modified carbon nanotubes, flaky silver powder, and modified expanded graphite. The modified carbon nanotubes are carboxylated carbon nanotubes. The modified expanded graphite is a composite material of ZIF-7 and expanded graphite.

[0051] Furthermore, the latent curing aid includes one or more of a phenolic amine curing agent and a curing accelerator, the diluent includes one or more of butyl glycidyl ether and phenyl glycidyl ether, the auxiliary agent includes ammonia water and a silane coupling agent, the curing accelerator includes one or both of SH-A100 or 2-ethyl-4-methylimidazole, SH-A100 is purchased from Guangzhou Xinxi Metallurgical Chemical Co., Ltd., and the silane coupling agent includes one or both of γ-glycidyloxypropyltrimethoxysilane or γ-aminopropyltriethoxysilane.

[0052] The method for preparing modified carbon nanotubes comprises the following steps: P1. Prepare a mixed acid solution by mixing 100 ml of concentrated nitric acid and 300 ml of concentrated sulfuric acid in a volume ratio of 1:3. Slowly add 2 g of multi-walled carbon nanotube solution into the mixed acid solution while stirring continuously. P2, ultrasonic treatment was performed at 50° C. for 4 hours. After the ultrasonic treatment was completed, the mixture was heated and stirred, and refluxed at 50° C. for 3 hours to obtain a reaction solution; P3. Slowly pour the reaction solution into a vessel containing 1L of deionized water, cool it, and then filter it. Rinse it with a large amount of deionized water until the pH is close to 7. Vacuum dry the acidified carbon nanotubes at 80°C for 12 hours to obtain carboxylated carbon nanotubes.

[0053] Specifically, the preparation method of modified expanded graphite is: Q1. Dissolve 0.6g zinc nitrate hexahydrate and 1.5g 2-methylimidazole in 30ml The mixture was added to methanol and stirred vigorously for 2 hours and then allowed to stand for 24 hours to allow the crystals to grow fully. After centrifugation, the mixture was washed three times with anhydrous methanol to obtain a white powder, which was then dried at 50°C in vacuum for 12 hours to obtain ZIF-7 crystals. Q2. Add 10g of natural flake graphite to 200ml of concentrated sulfuric acid, stir evenly, slowly add 10g of sodium nitrate, continue stirring and add 20g of potassium permanganate three times, control the temperature between 25℃ to avoid violent reaction. After 4 hours of reaction, add deionized water to dilute, and then add hydrogen peroxide to stop the reaction; after washing and drying, put it in a high-temperature furnace, heat it quickly at 800-1000℃ to make it expand, and obtain expanded graphite after cooling.

[0054] Q3, 1g of ZIF-7 and 1g of expanded graphite were added to 30ml of ethanol, 0.1g of polyvinyl pyrrolidone and 0.1g of 3-aminopropyltriethoxysilane were added, stirring was continued for 1 hour, and the mixture was placed in an ultrasonic cleaner and ultrasonicated for 30 minutes; Q4. Filter the mixed solution after ultrasonic treatment, collect the solid part, wash it with ethanol, and vacuum dry it at 60°C for 12 hours.

[0055] The preparation method of synthetic acrylic resin comprises the following steps: N1. Dissolve 40 parts of methyl acrylate, 10 parts of methyl methacrylate, 30 parts of glycidyl methacrylate, 15 parts of styrene and 5 parts of methacrylic acid monomer in 300 parts of ethyl acetate solvent according to weight proportions, add 0.5 parts of stabilizer 4-methoxyphenol, mix well and add to the reactor.

[0056] N2. Add 0.5 parts of dibenzoyl peroxide dropwise into the reactor; heat the reactor to 80°C and keep the temperature constant, continue stirring under constant temperature conditions, and the reaction time is 6 hours.

[0057] N3. After the reaction is completed, stop heating and let the mixture cool naturally to room temperature. Use a filter to filter the mixture to remove unreacted solid particles. Wash with an appropriate amount of ethyl acetate three times to remove unreacted raw materials and impurities. Dry the washed product in a vacuum drying oven to remove the solvent. The drying temperature is 80°C and the drying time is 24 hours until the product is completely dry.

[0058] The preparation method of the phenalkamine curing agent comprises the following steps: P1. Start by dissolving 100g of dicyandiamide in 200g of ethanol, then slowly add 50g of 37% formaldehyde solution and continue stirring. Add a few drops of hydrochloric acid catalyst and stir evenly.

[0059] P2. Under stirring conditions, gradually add 80 g of phenol, control the reaction temperature at 80°C, and adjust the pH value to pH 7 with dilute hydrochloric acid or sodium hydroxide solution, and continue to stir the reaction mixture under a neutral environment for 4 hours until the reaction is completed.

[0060] P3. After the reaction is completed, stop heating and let the mixture cool naturally to room temperature. Use a filter to filter the mixture to remove unreacted solid particles. Wash with an appropriate amount of ethanol solvent 3 times to remove unreacted raw materials and impurities. Dry the washed product in a vacuum drying oven to remove the solvent. The drying temperature is 80°C and the drying time is 24 hours until the product is completely dry.

[0061] The preparation method of the conductive adhesive comprises the following steps: S1. Add synthetic acrylic resin, epoxy resin, conductive filler and some additives to some diluents, put them into a double planetary mixer according to the weighed amount, and disperse them at high speed until all the materials are dissolved. The speed during high-speed dispersion is 400-600 rpm, and the high-speed dispersion time is 30-60 minutes.

[0062] S2. Add the latent curing agent, the remaining diluent and the remaining additives, mix well, first perform high-speed dispersion at 400-600 rpm until all materials are added, then use high-speed dispersion at a speed of 800-1200 rpm for 3.5-4.5 hours. Put the mixed conductive adhesive into the vacuum degassing equipment, vacuumize it, and keep the vacuum degree at about -0.09 MPa for 20 minutes until the bubbles disappear completely to remove the bubbles generated during the mixing process. Filter and package the conductive adhesive into suitable containers. Store at room temperature in a dry and ventilated environment.

[0063] The coating production process includes the following steps: Y1: unwinding the carrier film and coating the conductive adhesive; Y2: Drying, cooling, winding, packaging, and shipping of finished products.

[0064] After the conductive adhesive is coated on the carrier film and dried, in step Y2, the conductive adhesive is dried at 100° C. for 30 minutes. The conductive adhesive film layer has a thickness of 40 μm, and the carrier release film layer has a thickness of 60 μm.

[0065] The conductive components include steel sheet layer, conductive film layer, PI insulation layer and copper foil layer from top to bottom. The conductive adhesive on the carrier release film passes through a hot pressing roller with a temperature of 130 degrees, a pressure of 5 kg and a speed of 1 minute / meter, connecting one side of the conductive adhesive to the steel sheet. The conductive adhesive tape has the side of the carrier film. After the carrier release film is torn off, it is adhered to the PI surface. The fast pressing temperature of the conductive components is 180 degrees, pre-pressing for 10 seconds, forming for 150 seconds, and a pressure of 120 kg. After pressing, it is baked at 160 degrees for 70 minutes to make the product stable.

[0066] Table 1: Weight distribution ratio of the formula

[0067] Example 1 The preparation method of the conductive adhesive comprises the following steps: S1. Add synthetic acrylic resin, epoxy resin, conductive filler and silane coupling agent to 60 parts of butyl glycidyl ether, put them into a double planetary mixer according to the weighed parts, and disperse them at high speed until all the materials are dissolved. The speed during high-speed dispersion is 400 rpm and the high-speed dispersion time is 30 minutes.

[0068] S2. Add the latent curing agent, the remaining diluent and the remaining additives, mix well, first perform high-speed dispersion at 400 rpm until all materials are added, then use high-speed dispersion at 800 rpm for 3.5 hours. Put the mixed conductive adhesive into the vacuum degassing equipment, vacuumize it, keep the vacuum degree at about -0.09MPa, and last for 20 minutes until the bubbles disappear completely to remove the bubbles generated during the mixing process. Filter and package the conductive adhesive into suitable containers. Store at room temperature in a dry and ventilated environment.

[0069] Example 2 The preparation method of the conductive adhesive comprises the following steps: S1. Add synthetic acrylic resin, epoxy resin, conductive filler and silane coupling agent to 80 parts of butyl glycidyl ether, put them into a double planetary mixer according to the weighed parts, and disperse them at high speed until all the materials are dissolved. The speed during high-speed dispersion is 600 rpm and the high-speed dispersion time is 60 minutes.

[0070] S2. Add the latent curing agent, the remaining diluent and the remaining additives, mix well, first perform high-speed dispersion at 600 rpm until all materials are added, then use high-speed dispersion at a speed of 1200 rpm for 4.5 hours. Put the mixed conductive adhesive into the vacuum degassing equipment, vacuumize it, keep the vacuum degree at about -0.09MPa, and last for 20 minutes until the bubbles disappear completely to remove the bubbles generated during the mixing process. Filter and package the conductive adhesive into suitable containers. Store at room temperature in a dry and ventilated environment.

[0071] Example 3 The preparation method of the conductive adhesive comprises the following steps: S1. Add synthetic acrylic resin, epoxy resin, conductive filler and silane coupling agent to 50 parts of butyl glycidyl ether, put them into a double planetary mixer according to the weighed parts, and disperse them at high speed until all the materials are dissolved. The speed during high-speed dispersion is 500 rpm and the high-speed dispersion time is 50 minutes.

[0072] S2. Add the latent curing agent, the remaining diluent and the remaining additives, mix well, first perform high-speed dispersion at 500 rpm until all materials are added, then use high-speed dispersion at 1000 rpm for 4 hours. Put the mixed conductive adhesive into the vacuum degassing equipment, vacuumize it, keep the vacuum degree at about -0.09 MPa, and last for 20 minutes until the bubbles disappear completely to remove the bubbles generated during the mixing process. Filter and package the conductive adhesive into suitable containers. Store at room temperature in a dry and ventilated environment.

[0073] Example 4 The preparation method of the conductive adhesive comprises the following steps: S1. Add synthetic acrylic resin, epoxy resin, conductive filler and silane coupling agent to 50 parts of butyl glycidyl ether, put them into a double planetary mixer according to the weighed parts, and disperse them at high speed until all the materials are dissolved. The speed during high-speed dispersion is 4500 rpm and the high-speed dispersion time is 45 minutes.

[0074] S2. Add the latent curing agent, the remaining diluent and the remaining additives, mix well, first perform high-speed dispersion at 450 rpm until all materials are added, then use high-speed dispersion at 900 rpm for 3.5 hours. Put the mixed conductive adhesive into the vacuum degassing equipment, vacuumize it, keep the vacuum degree at about -0.09MPa, and last for 20 minutes until the bubbles disappear completely to remove the bubbles generated during the mixing process. Filter and package the conductive adhesive into suitable containers. Store at room temperature in a dry and ventilated environment.

[0075] Example 5 The preparation method of the conductive adhesive comprises the following steps: S1. Add synthetic acrylic resin, epoxy resin, conductive filler and silane coupling agent to 50 parts of phenyl glycidyl ether, put them into a double planetary mixer according to the weighed parts, and disperse them at high speed until all the materials are dissolved. The speed during high-speed dispersion is 550 rpm and the high-speed dispersion time is 55 minutes.

[0076] S2. Add the latent curing agent, the remaining diluent and the remaining additives, mix well, first perform high-speed dispersion at 550 rpm until all materials are added, then use high-speed dispersion at a speed of 1100 rpm for 4.5 hours. Put the mixed conductive adhesive into the vacuum degassing equipment, vacuumize it, and keep the vacuum degree at about -0.09MPa for 20 minutes until the bubbles disappear completely to remove the bubbles generated during the mixing process. Filter and package the conductive adhesive into suitable containers. Store at room temperature in a dry and ventilated environment.

[0077] Comparative Example 1 The main difference between Comparative Example 1 and Example 2 is that the synthetic acrylic resin is replaced by a commercially available acrylic resin in Comparative Example 1. The remaining steps and component parameters of Comparative Example 1 are the same as those of Example 2.

[0078] Comparative Example 2 The main difference between Comparative Example 2 and Example 2 is that the epoxy resin is replaced with commercially available epoxy resin E44 in Comparative Example 2. The remaining steps and component parameters of Comparative Example 2 are the same as those of Example 2.

[0079] Comparative Example 3 The main difference between Comparative Example 3 and Example 2 is that in Comparative Example 3, the conductive filler is changed to silver-coated polystyrene microspheres with an addition ratio of 70% and granular silver powder with 30%. The remaining steps and component parameters of Comparative Example 3 are the same as those of Example 2.

[0080] Comparative Example 4 The main difference between Comparative Example 4 and Example 2 is that the phenalkamine curing agent is replaced by a commercially available curing agent in Comparative Example 4. The remaining steps and component parameters of Comparative Example 4 are the same as those of Example 2.

[0081] Comparative Example 5 The main difference between Comparative Example 5 and Example 2 is that the curing accelerator is omitted in Comparative Example 5, and no curing accelerator is added in the conductive adhesive preparation step. The remaining steps and component parameters of Comparative Example 5 are the same as those of Example 2.

[0082] The above-mentioned embodiments and comparative examples were tested for performance, wherein the thickness before and after lamination was tested using a micrometer; the peel strength at 90 degrees was tested using lPC-TM-650-2.4.9, the solder heat resistance test method was lPC-TM-650-2.4.13, the transfer test method was a press, and for the grounding resistance (grounding hole Ф1.00mm), the test method after curing was a resistor meter, the test method for SMT 3 times was a reflow oven, a resistor meter, and the test method for 85°C, 85%RH, 96H was a high temperature and high humidity box, a resistor meter. The test data are shown in Tables 2 and 3: Table 2: Performance test results of Examples 1-5

[0083] Table 3: Performance test results of comparative examples 1-5

[0084] As can be seen from Table 2, by adding a latent curing aid in Example 1-Example 5, the potential possibility of the reaction of acrylic resin and epoxy resin at room temperature can be reduced, thereby improving the storage effect of the conductive adhesive without affecting its performance. In the test items in Table 2, the thickness of Example 1-Example 5 after lamination does not change much, the solder has good heat resistance, has transferability at 130°C, and has good conductivity. The conductive adhesive prepared in Example 1-Example 5 can improve the overall performance of electronic products and meet application scenarios with different needs. The preparation method of Example 1-Example 5 directly mixes raw materials such as acrylic resin, epoxy resin, conductive filler, additive, diluent and latent curing aid evenly during the preparation process without separate storage, which reduces production costs while simplifying the user's use process, and can improve the production efficiency and product quality of the conductive adhesive.

[0085] As can be seen from Table 3, compared with Example 2, Comparative Example 1 uses a commercially available ordinary acrylic resin, while the synthetic acrylic resin prepared in Example 2 is an acrylic resin used for conductive adhesives. By adjusting the ratio of monomers, it has better heat resistance, cross-linking density, and polar groups combined with other resins and fillers, so that the peel strength, heat resistance and conductive properties of Example 2 are better than those of Comparative Example 1.

[0086] Compared with Example 2, Comparative Example 2 uses a common epoxy resin on the market. The epoxy resin used in Example 2 contains a trifunctional alicyclic epoxy resin with stronger heat resistance and higher crosslinking density. The conductive adhesive after the crosslinking reaction has better mechanical properties, weather resistance, and electrical properties, so that the peel strength, heat resistance and conductivity of Example 2 are better than those of Comparative Example 2.

[0087] Compared with Example 2, Comparative Example 3 uses silver-coated polystyrene microspheres and granular silver powder. The silver-coated polystyrene microspheres, modified carbon nanotubes, silver powder, and modified expanded graphite used in Example 2 can improve the electrical properties of the conductive adhesive while reducing the cost. Since the conductive filler in Example 2 has a larger specific surface area than that in Comparative Example 3, the thickness change of the conductive adhesive after pressing can be small, and the conductive adhesive will not be locally uneven, thereby improving the mechanical properties of the conductive adhesive, so that the peel strength, heat resistance and conductivity of Example 2 are all better than those of Comparative Example 3.

[0088] Compared with Example 2, Comparative Example 4 uses a commercially available curing agent. Since the commercially available curing agent lacks latency, some materials react prematurely during storage of the conductive adhesive with low curing activity, resulting in system instability, stratification caused by instability between the diluent and the resin, and precipitation of some conductive filler components. Ultimately, in the process of preparing the conductive adhesive, the peel strength, heat resistance and conductivity of Comparative Example 4 are not superior to those of other comparative examples and examples.

[0089] Compared with Example 2, Comparative Example 5 omits the curing accelerator, which results in more curing activity energy being required to stimulate the reaction between the curing agent and the resin. Since the application of the present invention is to perform curing under specific temperature conditions, the curing degree of the conductive adhesive in Comparative Example 5 will be worse than that in Example 2. The peel strength, heat resistance and conductive properties of Comparative Example 5 are also worse than those of Example 2.

[0090] The above is a preferred embodiment of the present invention. Relevant personnel in this technical field may make several improvements and modifications without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A conductive adhesive, characterized in that: The invention is prepared from the following raw materials in parts by weight: 40-60 parts of synthetic acrylic resin, 5-15 parts of epoxy resin, 25-45 parts of conductive filler, 5-15 parts of latent curing auxiliary agent, 80-120 parts of diluent and 5-8 parts of auxiliary agent.

2. The conductive adhesive according to claim 1, characterized in that: The synthetic acrylic resin is synthesized from methyl acrylate, methyl methacrylate, glycidyl methacrylate, styrene and methacrylic acid.

3. The conductive adhesive according to claim 1, characterized in that: The epoxy resin includes trifunctional alicyclic epoxy resin and bisphenol A epoxy resin.

4. The conductive adhesive according to claim 1, characterized in that: The conductive filler comprises at least two or more of silver-coated polystyrene microspheres, modified carbon nanotubes, silver powder, and modified expanded graphite.

5. The conductive adhesive according to claim 1, characterized in that: The latent curing aid includes one or more of a phenolic amine curing agent and a curing accelerator, the diluent includes one or more of butyl glycidyl ether and phenyl glycidyl ether, the aid includes ammonia water and a silane coupling agent, the curing accelerator includes one or both of SH-A100 and 2-ethyl-4-methylimidazole, and the silane coupling agent includes one or both of γ-glycidyloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane.

6. The conductive adhesive according to claim 2, characterized in that: A method for preparing a synthetic acrylic resin, The following steps are included: N1. Dissolve the monomers in the solvent according to a predetermined ratio, mix them evenly and add them into the reactor; N2, add the initiator dropwise into the reactor; heat the reactor to a certain temperature and keep the temperature constant; N3. After the polymerization is completed, the product is cooled, washed and dried.

7. The conductive adhesive according to claim 3, characterized in that: The ratio of the trifunctional alicyclic epoxy resin to the bisphenol A epoxy resin of the epoxy resin is 3:7-5:

5.

8. The conductive adhesive according to claim 5, characterized in that: The preparation method of the phenalkamine curing agent comprises the following steps: P1. Dissolve dicyandiamide in a solvent, mix with formaldehyde, add a catalyst, and stir evenly; P2. Gradually add phenol under stirring conditions to maintain the reaction temperature and pH value; P3. After the reaction is completed, the mixture is cooled to room temperature, and the product is cooled, washed and dried.

9. A method for preparing a conductive adhesive according to any one of claims 1 to 8, characterized in that: The steps include: S1. Add synthetic acrylic resin, epoxy resin, conductive filler and part of the additives to part of the diluent, put them into a double planetary mixer according to the weighed number, and disperse them at high speed until all the materials are dissolved; S2. Add the latent curing agent, the remaining diluent and the remaining additives, mix well, then vacuum degas, filter and package, and store at room temperature in a dry and ventilated environment.

10. The use of the conductive adhesive according to any one of claims 1 to 8, characterized in that: The conductive adhesive is applied to the coating film production process.

Citation Information

Patent Citations

  • Low-halogen high-conductivity single-ingredient conductive gum

    CN102443370A

  • Conductive adhesive

    CN108659720A

  • Die bonding paste and semiconductor device using the same

    JP2008174577A

  • Low stress conductive adhesive

    US20060197066A1